2012
DOI: 10.1111/j.1461-0248.2012.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on tree ranges: model intercomparison facilitates understanding and quantification of uncertainty

Abstract: Model-based projections of shifts in tree species range due to climate change are becoming an important decision support tool for forest management. However, poorly evaluated sources of uncertainty require more scrutiny before relying heavily on models for decision-making. We evaluated uncertainty arising from differences in model formulations of tree response to climate change based on a rigorous intercomparison of projections of tree distributions in France. We compared eight models ranging from niche-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
195
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(209 citation statements)
references
References 45 publications
(105 reference statements)
9
195
2
3
Order By: Relevance
“…Incorporating the effects of rising CO 2 in models of future tree growth continues to be a major challenge. The sensitivity of projected productivity to assumptions regarding increased CO 2 was high in modelling studies of climate change impacts in commercial timber plantations in the Southern Hemisphere (Kirschbaum et al 2012;Battaglia et al 2009), and a recent analysis indicated a general convergence of different model predictions for future tree species distribution in Europe, with most of the difference between models due to the way in which this effect is incorporated (Cheaib et al 2012). Increased CO 2 has been shown to increase the water-use efficiency of trees, but this is unlikely to entirely offset the effects of increased water stress on tree growth in drying climates (Leuzinger et al 2011;Booth 2013).…”
Section: Ecosystem Responses To Climatementioning
confidence: 99%
“…Incorporating the effects of rising CO 2 in models of future tree growth continues to be a major challenge. The sensitivity of projected productivity to assumptions regarding increased CO 2 was high in modelling studies of climate change impacts in commercial timber plantations in the Southern Hemisphere (Kirschbaum et al 2012;Battaglia et al 2009), and a recent analysis indicated a general convergence of different model predictions for future tree species distribution in Europe, with most of the difference between models due to the way in which this effect is incorporated (Cheaib et al 2012). Increased CO 2 has been shown to increase the water-use efficiency of trees, but this is unlikely to entirely offset the effects of increased water stress on tree growth in drying climates (Leuzinger et al 2011;Booth 2013).…”
Section: Ecosystem Responses To Climatementioning
confidence: 99%
“…Alternatively, max(TSS) has been used as a criteria to select detection thresholds (Albouy 396 et al 2012;Cheaib et al 2012). From our results, we conclude that it would be unfair to 397 convert continuous predictions to binary at an arbitrary t = 0.5.…”
Section: Selection Of Detection Threshold 385mentioning
confidence: 61%
“…70 Evaluation of individual model accuracy is therefore still crucial, and objective 71 statistics are required for comparison between alternative modelling approaches (Hirzel et 72 al. 2006;Liu et al 2011;Cheaib et al 2012;Jiménez-Valverde 2012). Despite the wide 73 acceptance of some standard statistics, there is currently a strong on-going debate as to 74 their use (Allouche et al 2006;Lobo et al 2008;Jiménez-Valverde 2012).The "area 75 under the receiver operating characteristic curve" (AUC; Hanley & McNeil 1982) is a 76 statistic currently considered to be the standard method to assess the accuracy of 77 predictive distribution models (Jiménez-Valverde 2012).…”
Section: Introduction 53mentioning
confidence: 99%
“…In generale, numerosi modelli prevedono una rarefazione delle specie arboree temperate alle quote più basse, come conseguenza del CC, anche se persiste una notevole divergenza fra gli scenari di previsione, dovuta in buona parte ai diversi criteri con cui i modelli rappresentano l'effetto dell'aumento dell'anidride carbonica in atmosfera (Cheaib et al 2012). La maggior parte di questi esercizi di stima sotto scenari di CC sono stati comunque condotti su dati regionali a bassa risoluzione spaziale; le applicazioni su dati ad alta risoluzione sono poche (v. Ruiz-Labourdette et al 2012) e, a nostra conoscenza, carenti per il nostro paese.…”
unclassified
“…Incomplete appaiono pure le conoscenze circa l'impatto sulla biodiversità forestale di eventi climatici estremi, così come pone problemi la discriminazione fra gli effetti diretti delle variabili climatiche e quelli indiretti connessi ad altri processi potenzialmente modulati dal CC, quali i cambiamenti di uso del suolo, gli incendi, le deposizioni azotate, in grado di plasmare la biodiversità a scala di biocenosi, con particolare riferimento alla loro consistenza e continuità spaziale (v. Clavero et al 2011). In alcuni casi, è prefigurabile un effetto di rinforzo fra i vari fattori connessi al CC, con un esito complessivo che potrebbe portare alla marginalizzazione di specie arboree oggi ampiamente diffuse, e a cambiamenti nella fisionomia e nella continuità delle coperture forestali.…”
unclassified